Observation of strong electromagnetic fields around laser-entrance holes of ignition-scale hohlraums in inertial-confinement fusion experiments at the National Ignition Facility - C K Li; A B Zylstra; J A Frenje; F H Séguin; N Sinenian; R D Petrasso; P A Amendt; R Bionta; S Friedrich; G W Collins; E Dewald; T Döppner; et al. (New Journal of Physics, 2013)
Energy spectra and spectrally resolved one-dimensional fluence images of self-emitted charged-fusion products (14.7 MeV D ^3 He protons) are routinely measured from indirectly driven inertial-confinement fusion (ICF) experiments utilizing ignition-scaled hohlraums at the National Ignition Facility (NIF). A striking and consistent feature of these images is that the fluence of protons leaving the ICF target in the direction of the hohlraum's laser entrance holes (LEHs) is very nonuniform spatially, in contrast to the very uniform fluence of protons leaving through the hohlraum equator. In addition, the measured nonuniformities are unpredictable, and vary greatly from shot to shot. These observations were made separately at the times of shock flash and of compression burn, indicating that the asymmetry persists even at ∼0.5–2.5 ns after the laser has turned off. These phenomena have also been observed in experiments on the OMEGA laser facility with energy-scaled hohlraums, suggesting that the underlying physics is similar. Comprehensive data sets provide compelling evidence that the nonuniformities result from proton deflections due to strong spontaneous electromagnetic fields around the hohlraum LEHs. Although it has not yet been possible to uniquely determine whether the fields are magnetic ( B ) or electric ( E ), preliminary analysis indicates that the strength is ∼1 MG if B fields or ∼10 ^9  V cm ^−1 if E fields. These measurements provide important physics insight into the ongoing ignition experiments at the NIF. Understanding the generation, evolution, interaction and dissipation of the self-generated fields may help to answer many physics questions, such as why the electron temperatures measured in the LEH region are anomalously large, and may help to validate hydrodynamic models of plasma dynamics prior to plasma stagnation in the center of the hohlraum.